2003
DOI: 10.1074/jbc.m306815200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-independent CXCR2 Dimerization

Abstract: and the ʈIstituto di Neurobiologia Consiglio Nazionale delle Ricerche, Rome 00137, Italy Homo-and hetero-oligomerization have been reported for several G protein-coupled receptors (GPCRs). The CXCR2 is a GPCR that is activated, among the others, by the chemokines CXCL8 (interleukin-8) and CXCL2 (growth-related gene product ␤) to induce cell chemotaxis. We have investigated the oligomerization of CXCR2 receptors expressed in human embryonic kidney cells and generated a series of truncated mutants to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 48 publications
4
67
1
1
Order By: Relevance
“…Truncation of the B 1 receptor revealed that homo-oligomerization of this receptor, as determined by coimmunoprecipitation of differentially tagged receptors, is dependent on an epitope(s) lo- cated between residue Leu 26 on top of transmembrane helix 1 and Val 71 at the C-terminal end of intracellular loop 1. This epitope may be similar to that in the yeast ␣-factor receptor (Overton et al, 2003), C5a receptor (Klco et al, 2003), and CCR2 receptor (Mellado et al, 2001), which apparently require helix 1 for homo-oligomerization, or the CXCR2 receptor, which requires helix 3 (Trettel et al, 2003). On the other hand, the dopamine D2 receptor forms a symmetric dimer interface involving helix 4 (Guo et al, 2003), and the B 2 bradykinin receptor subtype apparently requires an epitope in the N-terminal domain (AbdAlla et al, 1999).…”
Section: Discussionmentioning
confidence: 72%
“…Truncation of the B 1 receptor revealed that homo-oligomerization of this receptor, as determined by coimmunoprecipitation of differentially tagged receptors, is dependent on an epitope(s) lo- cated between residue Leu 26 on top of transmembrane helix 1 and Val 71 at the C-terminal end of intracellular loop 1. This epitope may be similar to that in the yeast ␣-factor receptor (Overton et al, 2003), C5a receptor (Klco et al, 2003), and CCR2 receptor (Mellado et al, 2001), which apparently require helix 1 for homo-oligomerization, or the CXCR2 receptor, which requires helix 3 (Trettel et al, 2003). On the other hand, the dopamine D2 receptor forms a symmetric dimer interface involving helix 4 (Guo et al, 2003), and the B 2 bradykinin receptor subtype apparently requires an epitope in the N-terminal domain (AbdAlla et al, 1999).…”
Section: Discussionmentioning
confidence: 72%
“…The balance between homo-and heterodimers might therefore have a role in CXCL8 function; indeed, via CXCR1, CXCL8 selectively activates phospholipase D and the neutrophil respiratory burst (14,24), whereas CXCR2 is involved in CXCL8-mediated neutrophil migration (50). Cumulative evidence indicates that the dimerization of chemokine receptors should no longer be a matter of debate (4,5,7,10,12,51,52). Efforts should focus on studying the dynamics and functional relevance of receptor homo-and heterodimerization; understanding these concepts will change our view of chemokine receptor structure and activation, which is likely to have substantial influence on drug development and screening.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors have 77% overall sequence identity, but differ in their N-and C-terminal domains. Although initial reports suggested that only CXCR2 forms dimeric complexes (10,11), there is evidence that CXCR1 and CXCR2 form constitutive homo-and heterodimers with equal efficiency early in synthesis and maturation (12).…”
mentioning
confidence: 99%
“…The utility of deletion mutants has been demonstrated by different GPCR studies as receptor fragments can be expressed in a relatively native form (Marsango et al, 2011;Overton and Blumer, 2002;Trettel et al, 2003). Deletion mutants were: TM1-6 with a deletion in the region comprising the seventh TM helix, helix 8 and the C-terminal sequence, TM1-5 lacking the sixth and seventh TM helices, helix 8 and the C-terminal tail and TM1-4 missing the fifth, sixth and seventh TM helices, helix 8 and the C-terminal region.…”
Section: Loss Of Tms 5-7 Impairs Association With Wt Pkr2 In Yeastmentioning
confidence: 99%